Elämyksestä ideaksi - ideasta musiikiksi : sävellysprosessin yleinen malli ja sen soveltaminen Beatles -yhtyeen laulunteko- ja äänitysprosessiin - Heinonen, Yrjö (1995)
The thesis is based on three previously-published studies and this summary. A general model of the compositional process is outlined and it is applied to the songwriting and recording process of the Beatles. The model is based both on a cognitive theory of human action and a psychoanalytic theory of the processes which underly human behaviour. The model consists of two descriptions. The first is a stage-by-stage description of a typical compositional process, comprising at the most general level the following stages: precomposition, composition proper, and revision. The second description consists at the most general level of the following contextual factors: culture and historical situation (communal factors), personality traits and life situation (individual factors), and compositional task plus compositional conditions (compositional factors). The function of the contextual factors is to explain the deviations found in the individual compositional processes, as compared with the typical one. Both descriptions are considered to be inseparable parts of the model. The applied section of the study begins with summaries of the previously-published studies. In the first study, I explored to what degree certain models of the Lennon-McCartney ballad 'Michelle' were "only" stylistic, and to what degree it is reasonable to assume a direct influence between a certain model and 'Michelle'. In study II the typical writing and recording process of a typical Lennon-McCartney song was described, and certain contextual factors were also examined. In study III the genesis of 'Michelle' was described using the stage-by-stage description outlined in study II. Further, the autobiographical background of 'Michelle', as well as of certain other McCartney songs was examined. The summaries are followed by a brief review of the cultural and musico-historical context in which the Beatles were founded, in which they functioned and which they influenced. The applied section of the study ends with a brief review of the personalities of Lennon and McCartney, as well as of some normative and non-normative processes and events (life-span, group processes, losing loved ones, meeting influential persons) and their influence on the songwriting and recording process. In conclusion it may be stated that the general model of the compositional process - including both the stage-by-stage description and the contextual factors - works quite well as a frame of reference when applied to the songwriting and recording process of the Beatles.